2022
DOI: 10.1002/advs.202204718
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐II Excitation Phototheranostic Platform for Synergistic Photothermal Therapy/Chemotherapy/Chemodynamic Therapy of Breast Cancer Bone Metastases

Abstract: To improve bone metastases treatment efficacy, current strategies are focused on the integration of chemotherapy with phototheranostic. However, the success of phototheranostic approaches is hampered by the limited tissue penetration depth of near-infrared-I (NIR-I) light (700-900 nm). In this study, a NIR-II (1000-1700 nm) excitation phototheranostic (BTZ/Fe 2+ @BTF/ALD) is presented for NIR-II fluorescence imaging and NIR-II photoacoustic imaging-guided NIR-II photothermal therapy (PTT), chemotherapy, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…(B) Schematic illustration of 1064 nm light-activated NIR-II phototheranostic nanoplatform (BTZ/Fe2+@BTF/ALD) for combined NIR-II PTT/chemotherapy/CDT of breast cancer bone metastases. Reproduced under the terms of the http://creativecommons.org/licenses/by/4.0/ License 221 , published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) Schematic illustration of 1064 nm light-activated NIR-II phototheranostic nanoplatform (BTZ/Fe2+@BTF/ALD) for combined NIR-II PTT/chemotherapy/CDT of breast cancer bone metastases. Reproduced under the terms of the http://creativecommons.org/licenses/by/4.0/ License 221 , published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Methodsmentioning
confidence: 99%
“…In order to improve the therapeutic effect of bone metastases, the current treatment strategy mainly focuses on the combination of chemotherapy and phototherapy, in order to overcome the limited tissue penetration depth of NIR-I light, Professor Fan et al jointly reported a phototherapy nanoparticle (BTZ/Fe 2+ @BTF/ALD) for NIR-II fluorescence imaging and NIR-II photoacoustic imaging-guided NIR-II PTT, chemotherapy and CDT of breast cancer bone metastasis 221 . This phototherapy was performed by integrating dopamine-modified NIR-II absorption of donor-receptor-donor small molecules (BBT-FT-DA), borate anticancer drug Bortezomib (BTZ), and Fe 2+ as CDT catalysts into a bone-targeted ligand alendronate modified amphiphilic pegylated phospholipid.…”
Section: Cdt-based Combination Therapymentioning
confidence: 99%
“…8,9 However, the conventional PDT effect depends greatly on the PS, which is usually activated by UV or visible light that has low tissue penetration and high phototoxicity. In contrast, near-infrared (NIR) light, which can be divided into two biological windows, i.e., the first NIR (NIR-I: 700−950) and the second NIR (NIR-II: 1000−1700) biological windows, 10,11 has a higher tissue penetration depth owing to the low scattering and absorption of light by body tissues. 12 Therefore, the development of new PS agents that absorb the light in the NIR range is one of the highly pursued goals in PDT, while the CDT depends on the Fenton/Fentonlike reaction or is based on the catalysis of the materials that can decompose hydrogen peroxide (H 2 O 2 ) to hydroxyl radical (•OH) and 1 O 2 , which enhances the PDT effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PDT effect relies on the photosensitizer (PS), which converts the oxygen (O 2 ) to toxic ROS, especially singlet oxygen ( 1 O 2 ), which oxidizes the cancer cell and leads to cell death upon the light irradiation with an appropriate wavelength. , However, the conventional PDT effect depends greatly on the PS, which is usually activated by UV or visible light that has low tissue penetration and high phototoxicity. In contrast, near-infrared (NIR) light, which can be divided into two biological windows, i.e., the first NIR (NIR-I: 700–950) and the second NIR (NIR-II: 1000–1700) biological windows, , has a higher tissue penetration depth owing to the low scattering and absorption of light by body tissues . Therefore, the development of new PS agents that absorb the light in the NIR range is one of the highly pursued goals in PDT, while the CDT depends on the Fenton/Fenton-like reaction or is based on the catalysis of the materials that can decompose hydrogen peroxide (H 2 O 2 ) to hydroxyl radical (•OH) and 1 O 2 , which enhances the PDT effect. Nevertheless, the low catalytic efficiency and off-target side effect of the Fenton reaction limit the biomedical application of CDT .…”
Section: Introductionmentioning
confidence: 99%
“…It has been verified that heat can accelerate the Fenton reaction for amplified CDT. Thus, combining PTT with CDT may achieve greater therapeutic outcomes. However, the construction of organic materials doped with metal ions for chemodynamic–photothermal combined therapy has been limited to a number of studies, which mainly focused on NIR-I. …”
mentioning
confidence: 99%